Bioconversion of food waste to energy : a review - Kiran, Esra Uçkun (2015)
According to Food and Agricultural Organization (FAO), one third of food produced globally for human consumption is lost along the food supply chain. In many countries food waste are currently landfilled or incinerated together with other combustible municipal wastes for possible recovery of energy. However, these two approaches are facing more and more economic and environmental stresses. Due to its organic- and nutrient-rich composition, theoretically food waste can be utilized as a useful resource for production of biofuel through various fermentation processes. So far, valorization of food waste has attracted increasing interest, with biogas, hydrogen, ethanol and biodiesel as final products. Therefore, this review aims to examine the state-of-the-art of food waste fermentation technologies for renewable energy generation.